2016
DOI: 10.12659/pjr.895570
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocephalus and Pneumorrhachis After Spinal Surgery

Abstract: SummaryBackgroundPneumocephalus and pneumorrhachis are rare complications of neurosurgery. When a closed system such as the head and spinal area get injuried, it becomes open and the air can come in through that opening. In this case, we present a case of pneumocephalus and pneumorrhachis after spinal fusion surgery.Case ReportHerein we present a case of diagnosis and treatment of pneumocephalus and pneumorrhachis after spinal fusion surgery.ConclusionsOur patient developed postoperative pneumocephalus and pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…These are usually due to dura injury. 1) As in our case, after removal of the spinal intradural tumor, it is thought that air contact due to the openness of the surgical field and subsequent intradural compression of the air caused pneumocephalus. 10) The first complication that should be considered when an early confusion table develops after spinal surgery is pneumocephalus.…”
Section: Discussionsupporting
confidence: 51%
“…These are usually due to dura injury. 1) As in our case, after removal of the spinal intradural tumor, it is thought that air contact due to the openness of the surgical field and subsequent intradural compression of the air caused pneumocephalus. 10) The first complication that should be considered when an early confusion table develops after spinal surgery is pneumocephalus.…”
Section: Discussionsupporting
confidence: 51%
“…Only two cases have been reported in the literature presenting with both of these findings concomitantly after lumbar spine surgery. Only one of these had a late presenting dural leak [1,2]. We report such a rare case, only the second in literature, having the peculiarity of association with a late presenting dural leak and the involvement of both cervical, as well as lumbar regions of the spine.…”
Section: Introductionmentioning
confidence: 73%
“…Though a few cases of pneumocephalus after spine surgery have been reported, only one case report of pneumorachis after an incidental durotomy has been documented in the existing literature [1,5]. The presence of both pneumocephalus and pneumorachis after primary spine surgery is even more rare with only two cases reported till date [1,2]. In a case report by Karavelioglu et al [1], these complications were recognized in the immediate postoperative period on day 1 with symptoms of pneumocephalus but pneumorachis was asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumocephalus has been reported after traumatic injuries, spinal anesthesia and accidental dural puncture whilst performing epidural analgesia and epidural steroid injections. [3][4][5][6][7] However, there are only a few case reports that describe it after lumbar spine surgery. Akyüz et al described a case of delayed pneumocephalus and pneumorrhachis 2 months after lumbar spinal fusion surgery secondary to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Akyüz et al described a case of delayed pneumocephalus and pneumorrhachis 2 months after lumbar spinal fusion surgery secondary to infection. 6 Karavelioglu et al reported a case of pneumocephalus after lumbar disc surgery with pedicle screw fixation, where they postulated that they may have inadvertently torn open the arachnoid layer while trying to retrieve a large disc fragment. 7 In another case, diffuse pneumocephalus after posterior lumbar surgery for spinal stenosis was seen, where dural tear was noted intraoperatively and repaired.…”
Section: Discussionmentioning
confidence: 99%